2011
DOI: 10.5713/ajas.2011.11038
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance, Carcass Traits and Meat Quality of Slower-growing and Fast-growing Chickens Raised with and without Outdoor Access

Abstract: The objective of this study was to determine the effect of genotype (slower-growing vs. fast-growing) and production system (access to outdoors vs. indoor) on the growth performance, carcass yield and meat quality (chemical composition, physicochemical and sensory properties) of chickens. The experiment was performed on 1,040 day-old hybrid male chickens of two genotypes. Slower-growing chickens (Hubbard JA957, certified) and fast-growing chickens (Hubbard F15) were fed identical diets until 65 days of age. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
82
3
17

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(130 citation statements)
references
References 28 publications
28
82
3
17
Order By: Relevance
“…On day 84, a lower live weight with a worse feed conversion rate was observed in broilers in outdoor groups in accordance with other studies (Castellini et al 2002a(Castellini et al , 2002bWang et al 2009). In contrast to our results, outdoor access did not affect the growth performance in previous studies (Jiang et al 2011;Mikulski et al 2011;Chen et al 2013). Our findings could be explained by some factors in the outdoor system such as environmental temperature, exercise, pasture intake (Chen et al 2013).…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…On day 84, a lower live weight with a worse feed conversion rate was observed in broilers in outdoor groups in accordance with other studies (Castellini et al 2002a(Castellini et al , 2002bWang et al 2009). In contrast to our results, outdoor access did not affect the growth performance in previous studies (Jiang et al 2011;Mikulski et al 2011;Chen et al 2013). Our findings could be explained by some factors in the outdoor system such as environmental temperature, exercise, pasture intake (Chen et al 2013).…”
Section: Discussioncontrasting
confidence: 56%
“…Besides, in the outdoor group as a result of activity, abdominal fat was found to be lower than the indoor group. Conversely, it was reported that access to outdoor did not have an effect on abdominal fat (Grashorn & Brose 1997;Mikulski et al 2011). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Segundo Veloso et al (2014), isso pode prejudicar a comercialização destes animais, pois o consumidor brasileiro de frango caipira demanda principalmente o frango inteiro e uma carcaça não muito grande. O arraçoamento à vontade também pode fazer com que a ave não sinta a necessidade de procurar o alimento na área de pastejo disponível, podendo não adquirir atributos importantes esperados nestes animais, como coloração mais acentuada da carcaça e firmeza e sabor característicos da carne (Mikulski et al, 2011).…”
Section: óCiounclassified
“…O bem-estar na produção de aves está diretamente relacionado com o sistema de criação (Moura et al, 2010;Fraser et al, 2013). O sistema de semiconfinamento permite que as aves tenham livre acesso às áreas de pastejo, para que estas expressem seus comportamentos naturais, resultando em diferenças particulares na qualidade da carne, quando comparadas com as aves criadas confinadas (Fanatico et al, 2007;Mikulski et al, 2011). Por outro lado, as condições ambientais podem interferir no bem-estar, saúde e comportamento das aves, podendo se refletir em suas características fisiológicas e produtivas (Fouad et al, 2008;Tan et al, 2010).…”
Section: Introductionunclassified